Estudio de la variabilidad del ritmo cardíaco y la actividad electrodérmica en episodios de somnolencia (2017)
It is widely known that many traffic accidents occur every year in the world, and the drowsiness or sleepiness cause an 7% of road fatalities. In the last years, the monitoring and the detection of biological or physiological signals was being studied in preventive car safety. This project is based in the adquisition and the research of the behavioral patterns of this two signals in conditions of drowsiness. For this research, it was necessary the participation of 20 people who had certain specific clinical conditions to take the data. Once the information was already available, the information was processed to extract relevant parameters. Finally, trends were sought with statistical.